2018
DOI: 10.18632/aging.101442
|View full text |Cite
|
Sign up to set email alerts
|

A novel functional polymorphism of GFAP decrease glioblastoma susceptibility through inhibiting the binding of miR-139

Abstract: Glioblastoma (GBM) is the most commonly diagnosed solid tumor outside the central nervous system. However, genetic factors underlying GBM remain largely unclear. Previous studies indicated that Glial fibrillary acidic protein (GFAP) might play an important role in the aggressiveness of GBM and also contributed to its poor overall survival. The present study aims to test (1) the associations between GFAP single nucleotide polymorphisms (SNPs) and GBM cells chemoresistance and metastasis, and (2) the molecular m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…A growing number of evidences revealed that GFAP level increased in high-grade brain tumors, implying the important role of GFAP in the aggressiveness of brain tumors [4143]. It is reported that via interfering the binding of miR-139 and 3′UTR, variant G allele of rs11558961 that reduced GFAP expression contributes to low GFAP expression, and further inhibits the chemo-resistance and metastasis of glioblastoma (GBM) cells [44]. Additionally, the results of our study suggested that inhibiting miR-103a expression can attenuate injury of hippocampal neurons in epilepsy rats, which is reflected by the results that the mRNA expression of IL-6 and TNF-α decreased significantly in the hippocampus tissues of rats in the EP + miR-103a inhibitors group.…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of evidences revealed that GFAP level increased in high-grade brain tumors, implying the important role of GFAP in the aggressiveness of brain tumors [4143]. It is reported that via interfering the binding of miR-139 and 3′UTR, variant G allele of rs11558961 that reduced GFAP expression contributes to low GFAP expression, and further inhibits the chemo-resistance and metastasis of glioblastoma (GBM) cells [44]. Additionally, the results of our study suggested that inhibiting miR-103a expression can attenuate injury of hippocampal neurons in epilepsy rats, which is reflected by the results that the mRNA expression of IL-6 and TNF-α decreased significantly in the hippocampus tissues of rats in the EP + miR-103a inhibitors group.…”
Section: Discussionmentioning
confidence: 99%
“…Involvement of another miRNA, miR-139, was pursued by Wang J et al (2018). In a search for SNPs associated with risk for glioblastoma, they identified a C/G polymorphism in the 3'UTR of GFAPa at þ8182.…”
Section: Regulation Of Mrna Translation Micrornamentioning
confidence: 99%
“…Relevant teams analyzed the glioma data obtained from TCGA and verified the expression of differential proteins in the tissues or body fluids of glioma patients, animal models and cell lines. Common targets are GFAP ( Wang et al, 2018 ), HSP70 ( Sharifzad et al, 2020 ), VEGF ( Nicolas et al, 2019 ), BDNF ( Huo & Chen, 2019 ), ECM ( Tejero et al, 2019 ), FN1 ( Yu et al, 2020 ; Gu, Gu & Shou, 2014 ; Guo, Heller & Thorslund, 2016 ; Liao et al, 2018 ), CD44 ( Mooney et al, 2016 ), Fransgelin-2, Short Hairpin RNAGLN and GRN ( Ness, Riemenschneider & Baches., 2009 ; Trigos et al, 2019 ) etc. Previous research suggested that TAGLN2 might be involved in progression due to its higher expression in glioblastomas compared to IDH1/2 WT gliomas of lower grades ( Beyer et al, 2018 ; Han et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%